Catastrophic Reversible Cerebral Vasoconstriction Syndrome Associated With Serotonin Syndrome. Issue 9 (3rd September 2013) - John, Seby; Donnelly, Megan; Uchino, Ken
<x xml:space="preserve">Abstract</x> Objectives To report fulminant cases of reversible cerebral vasoconstriction syndrome (RCVS) in the setting of serotonin syndrome. Background RCVS is characterized by acute onset of severe headaches, with or without neurologic deficit, with evidence of reversible cerebral vasoconstriction. It is often benign, and prognosis is generally considered favorable. In the largest prospective study on RCVS, only 4% of patients were disabled from strokes and there were no fatalities. Methods We report a case series. Results We report 2 women with history of depression on selective serotonin re‐uptake inhibitors who presented with thunderclap headache and dizziness, respectively. Through the course of hospitalization, both patients developed rigidity, diaphoresis, fever, tachycardia with labile blood pressures and clonus on examination. Since there was a recent addition/increase in a known serotonergic agent, they met criteria for serotonin syndrome. Cerebrovascular imaging in both patients revealed severe multi‐focal vessel narrowing. The first patient developed large bi‐hemispheric ischemic infarcts and increased intra‐cranial pressure that was refractory to management, and she eventually expired. The second patient developed bilateral parieto‐occipital strokes and decerebrate posturing. Her course slowly stabilized, and she was eventually discharged with residual left‐sided hemiparesis. Repeat cerebrovascular imaging 1 month later showed normal vessels. In both patients, intra‐arterial nicardipine infusion improved angiographic appearance of stenoses, consistent with RCVS. Conclusions Both cases satisfied the Sternbach criteria for serotonin syndrome. Fatality in case 1 prevents demonstration of reversal of cerebral vasoconstriction, but improvement of arterial diameters with intra‐arterial calcium channel blockers in both cases suggests that both had RCVS. Serotonergic agents are known triggers of RCVS, but the concurrent presence of serotonin syndrome likely precipitated the malignant course in our patients. Severe clinical and angiographic manifestations should be considered as part of the spectrum of RCVS.